2020
DOI: 10.3168/jds.2019-17372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amount of milk replacer fed and the processing of corn in starter on growth performance, nutrient digestibility, and rumen and fecal fibrolytic bacteria of dairy calves

Abstract: The aim of this study was to evaluate effects of milk replacer (MR) feeding rate and processing of corn in calf starter (CS) on growth performance, nutrient digestibility, and rumen and fecal fibrolytic bacteria in dairy calves. Holstein male calves (n = 48, 2-3 d of age) were randomly assigned to 1 of 4 treatments with a 2 × 2 factorial arrangement of MR level of 0.749 kg of MR/d (LO) or up to 1.498 kg of MR/d (HI); and whole corn or flaked corn in textured CS. Calves were weaned by reducing MR offered by 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
2
18
2
Order By: Relevance
“…In line with previous studies, temporarily higher glucose and TG concentrations were observed with an intensified MR feeding rate of solids at approximately 0.75 kg/d relative to ad libitum feeding (Schäff et al, 2016;Frieten et al, 2017). Plasma BHB concentrations, an indicator of rumen development and starter intake, increase with SF intake (Deelen et al, 2016) and accordingly BHB paralleled SF intake in our study (Tümmler et al, 2020). The higher plasma NEFA concentrations in 10%-MR calves preweaning in wk 2 are in parallel with the findings of Schäff et al (2016) and Frieten et al (2017), who compared MR feeding rates of solids at approximately 0.75 kg/d with ad libitum feeding.…”
Section: Plasma Metabolites and Salivary Cortisolsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies, temporarily higher glucose and TG concentrations were observed with an intensified MR feeding rate of solids at approximately 0.75 kg/d relative to ad libitum feeding (Schäff et al, 2016;Frieten et al, 2017). Plasma BHB concentrations, an indicator of rumen development and starter intake, increase with SF intake (Deelen et al, 2016) and accordingly BHB paralleled SF intake in our study (Tümmler et al, 2020). The higher plasma NEFA concentrations in 10%-MR calves preweaning in wk 2 are in parallel with the findings of Schäff et al (2016) and Frieten et al (2017), who compared MR feeding rates of solids at approximately 0.75 kg/d with ad libitum feeding.…”
Section: Plasma Metabolites and Salivary Cortisolsupporting
confidence: 92%
“…The higher MEI and MEI/mBW reflect the overall improved energy and nutrient supply in 20%-MR fed calves, thus providing the condition for a potential metabolic imprinting as proposed in the review by Soberon and Van Amburgh (2013). The lower MR intake in the 10%-MR group lead to higher DMI of SF (hay, concentrate, and TMR) preweaning in wk 6 to 10, whereas postweaning DMI levels of SF were mostly higher in the 20%-MR group (Tümmler et al, 2020). Although the 10%-MR fed group revealed higher DMI of SF preweaning, which was similarly observed as a linear increase of forage intake with MR reduction (Broesder et al, 1990) or in a model for starter intake (Silva et al, 2019), this effect was not sufficient to compensate for the lower energy intake with MR in this group.…”
Section: Metabolizable Energy Intake and Growth Performancementioning
confidence: 80%
See 1 more Smart Citation
“…In summary, increased total and specific VFA concentrations, in combination with the notably low levels of fecal starch, may reflect both the starch and fiber levels of the dry diet, as well as the smooth transition to the postweaning diet. These low levels of fecal starch and smooth weaning transition may have led to greater capacity for forestomach starch digestion compared with other studies that weaned calves abruptly and report elevated fecal starch during the weeks and months following weaning van Niekerk et al, 2020).…”
Section: Effects Of Postweaning Plane Of Nutritionmentioning
confidence: 58%
“…Because calves were unable to consume enough ME from CS, calf performance was depressed and no differences were observed in calf BW for wk 5, 6, 7, and 8. Growth depression during weaning has been reported by others in calves fed a high MR feeding rate preweaning (Cowles et al, 2006;van Niekerk et al, 2020). It is important to note that the time of weaning and the weaning method also play key roles in CS intake and performance (Meale et al, 2015;Steele et al, 2017;Welboren et al, 2019).…”
Section: Discussionmentioning
confidence: 77%